The Hispanic American Historical Review (JSTOR)
Founded in 1918, the Hispanic American Historical Review (HAHR) pioneered the study of Latin American history and culture in the United States. Today it maintains a distinguished tradition of publishing vital work across thematic, chronological, regional, and methodological specializations, and it stands as the most widely respected journal in the field.
Keywords: Latin American Studies